The quiet revolution: Send-down movement and female empowerment in China - Chong Liu; Wenyi Lu; Ye Yuan (Journal of Development Economics, 2024)
What promotes female empowerment and gender equality? We investigate how internal population mobility and social interaction foster the advancement of female empowerment and gender equality across diverse subpopulations. Using the urban-to-rural youth resettlement program in China during the 1970s — the Send-down Movement — as our empirical context, we find that rural females with greater exposure to urban youths have achieved higher levels of education, increased labor force participation, greater financial independence, enhanced autonomy in marital and fertility decisions, increased political engagement, heightened self-confidence, reduced risk aversion, and a stronger belief in gender-equal ideologies and social values. Our findings underscore the role of population mobility in disseminating gender-equal ideologies and practices, both through human capital formation and social interactions, leading to lasting impacts on female empowerment in traditional societies.